Beothuk-European Contact in the 16th Century:: A Re-evaluation of the Documentary Evidence - Gilbert, William (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2011)
Abstract It is generally believed that hostility between Newfoundland’s Beothuk people and Europeans had its origin in the protohistoric period. This article re-evaluates the documentary evidence from the 16th century in order to assess this notion. Although the sources are fragmentary and often difficult to interpret, the evidence indicates that early Beothuk-European relations were not characterized by hostility and that the well-documented instances of hostility between the Beothuk and Newfoundland settlers during the late 18th and early 19th centuries have been wrongly assumed to indicate a state of perpetual conflict that extended back to the contact period.